Using a design structure matrix to support technology roadmapping for product–service systems - Son, Heungwook; Kwon, Yongjin; Park, Sang C.; Lee, Sungjoo (Technology Analysis and Strategic Management, 2018)
In light of the increasing trend of the use of the product–service system (PSS), tools that can help to analyse complex relationships among products, services and technologies and furthermore support decision-making during their planning are needed. To meet these needs, this study proposes a design structure matrix (DSM)-based technology roadmap (TRM) approach and a case study on mobile services is conducted. While PSS planning may involve a number of teams and organisations, the DSM-based TRM can help with such complex collaborative technology planning and hence lead to better performance. Methodologically, this is one of the first attempts to link DSM and TRM, both of which are widely used in planning stages, and thus is expected to contribute to the advances in TRM methodologies. In practice, this study describes an overall roadmapping process for the PSS, thus providing worthwhile guidelines available to organisations that are in charge of the TRM.
Keywords: design structure matrix; planning; product–service integrated system; relationship; Technology roadmap